Attenuated Toxoplasma gondii stimulates immunity to pancreatic cancer by manipulation of myeloid cell populations - Sanders, Kiah L. (Cancer Immunol Res, 2015)
Suppressive myeloid cells represent a significant barrier to the generation of productive antitumor immune responses to many solid tumors. Eliminating or reprogramming suppressive myeloid cells to abrogate tumor-associated immune suppression is a promising therapeutic approach. We asked whether treatment of established aggressive disseminated pancreatic cancer with the immunotherapeutic attenuated Toxoplasma gondii vaccine strain CPS would trigger tumor-associated myeloid cells to generate therapeutic antitumor immune responses. CPS treatment significantly decreased tumor-associated macrophages and markedly increased dendritic cell infiltration of the pancreatic tumor microenvironment. Tumor-resident macrophages and dendritic cells, particularly cells actively invaded by CPS, increased expression of co-stimulatory molecules CD80 and CD86 and concomitantly boosted their production of IL12. CPS treatment increased CD4(+) and CD8(+) T-cell infiltration into the tumor microenvironment, activated tumor-resident T cells, and increased IFNγ production by T-cell populations. CPS treatment provided a significant therapeutic benefit in pancreatic tumor-bearing mice. This therapeutic benefit depended on IL12 and IFNγ production, MyD88 signaling, and CD8(+) T-cell populations. Although CD4(+) T cells exhibited activated effector phenotypes and produced IFNγ, CD4(+) T cells as well as NK cells were not required for the therapeutic benefit. In addition, CD8(+) T cells isolated from CPS-treated tumor-bearing mice produced IFNγ after re-exposure to pancreatic tumor antigen, suggesting this immunotherapeutic treatment stimulated tumor cell antigen-specific CD8(+) T-cell responses. This work highlights the potency and immunotherapeutic efficacy of CPS treatment and demonstrates the significance of targeting tumor-associated myeloid cells as a mechanism to stimulate more effective immunity to pancreatic cancer.